Plasma Homocysteine, Folate and Vitamin B12 in Different Trimester of Pregnancy (Bangladesh Journal of Nutrition, 2012)
The present study has been undertaken to investigate plasma creatinine, folate and vitamin B12 as underlying factors in the reduction of plasma homocysteine concentration in different trimesters of pregnancy. Under a cross-sectional design, 30 healthy nonpregnant as well as 130 pregnant women, at 3 different trimesters of pregnancy (43 in 1st trimester, 44 in 2nd trimester and 43 in 3rd trimester) were sampled for plasma levels of folate, vitamin B12, homocysteine and creatinine. Plasma homocysteine and creatinine level were significantly (p